ANALISIS FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGKATAN KERJA PADA SEKTOR INDUSTRI DI JAWA BARAT - Shaffa, Salsa Zahira; Abdullah, Mirna Nur Alia (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2023)
The industrial sector is one of the economic sectors that should be a sector that can lead other economic sectors to develop and improve. As the heart of the national industry, West Java Province is very densely populated with industrial areas. It is not surprising that West Java Province is a significant producer of Gross Regional Domestic Product (GRDP). Basically, the industrial sector has an important role in a regional economic development. The main objective is to imcrease the number of jobs for workers of productive age who have not yet found a job. Increased employment in the industrial sector. There are many factors in the absorption of the industrial sector workforce in West Jawa Province. To find out these problems, this articels uses the Literature Review method. This method is used to search for journal article serach uses relevant previous research and gets 10 articeles to be analyzed. The results of research journals that have beenanalyzed, it can be concluded that the factors that influence the absorption of the workforce in West Java Province, namely, such as the number of business units, wage levels, investment, Gross Regional Domestic Product (GRDP), and Human Development Index (IPM).